Genetic Algorithm Based Decentralized Task Assignment for Multiple Unmanned Aerial Vehicles in Dynamic Environments - Choi, Hyun-Jin; Kim, You-Dan; Kim, Hyoun-Jin (International journal of aeronautical and space sciences, 2011)
Task assignments of multiple unmanned aerial vehicles (UAVs) are examined. The phrase “task assignment” comprises the decision making procedures of a UAV group. In this study, an on-line decentralized task assignment algorithm is proposed for an autonomous UAV group. The proposed method is divided into two stages: an order optimization stage and a communications and negotiation stage. A genetic algorithm and negotiation strategy based on one-to-one communication is adopted for each stage. Through the proposed algorithm, decentralized task assignments can be applied to dynamic environments in which sensing range and communication are limited. The performance of the proposed algorithm is verified by performing numerical simulations. KCI Citation Count: 1